2020
DOI: 10.3389/fnagi.2020.00273
|View full text |Cite
|
Sign up to set email alerts
|

Dropout in Neural Networks Simulates the Paradoxical Effects of Deep Brain Stimulation on Memory

Abstract: Neuromodulation techniques such as deep brain stimulation (DBS) are a promising treatment for memory-related disorders including anxiety, addiction, and dementia. However, the outcomes of such treatments appear to be somewhat paradoxical, in that these techniques can both disrupt and enhance memory even when applied to the same brain target. In this article, we hypothesize that disruption and enhancement of memory through neuromodulation can be explained by the dropout of engram nodes. We used a convolutional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…Here, we employed a systematic approach to examine the temporal specificity of prelimbic cortex DBS administration and isolate the effects of DBS on the consolidation of memory by stimulating post acquisition. We also showed consistent results across multiple models of conditioned fear and in repeat experiments, which is important given the paradoxical ability of DBS to both enhance and disrupt memories (Tan, Du, et al, 2020;Tan, Fung, et al, 2020;Tan, Neoh, et al, 2020). Despite the limitations of using conditioned fear to model anxiety disorders (LeDoux, 2015), it is one of the most wellestablished and translatable models currently available (Ganella & Kim, 2014).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Here, we employed a systematic approach to examine the temporal specificity of prelimbic cortex DBS administration and isolate the effects of DBS on the consolidation of memory by stimulating post acquisition. We also showed consistent results across multiple models of conditioned fear and in repeat experiments, which is important given the paradoxical ability of DBS to both enhance and disrupt memories (Tan, Du, et al, 2020;Tan, Fung, et al, 2020;Tan, Neoh, et al, 2020). Despite the limitations of using conditioned fear to model anxiety disorders (LeDoux, 2015), it is one of the most wellestablished and translatable models currently available (Ganella & Kim, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…However, few studies have systematically investigated the effects of DBS on fear memory. We previously hypothesized that DBS would be able to disrupt memories through the disruption of the engram process (Tan, Du, et al, 2020;Tan, Fung, et al, 2020;Tan et al, 2019). In this study, we examined the effects of DBS on the prelimbic cortex, which is a structure that is considered to be an ideal target (Lim et al, 2011;Tan et al, 2019) for the disruption of fear memories, as it is implicated in the expression of learned but not innate fear (Corcoran & Quirk, 2007).…”
mentioning
confidence: 99%
“…The stimulation parameters (chronic high-frequency stimulation) used in this study were based on our previous experiments [7]. We previously showed chronic DBS could enhance memory in middle-aged animals [7], and hypothesised that the effects of chronic DBS on memory circuitry would enhance rather than disrupt memories [13,26]. Furthermore, the use of high-frequency stimulation rather than lowfrequency stimulation was based on our previous data that suggested possible anxiogenic effects (decreased time spent in the centre zone of the OFT) with low-frequency ventromedial prefrontal cortex (vmPFC) stimulation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, individual animals were placed in the middle of the open field (100 × 100 × 40 cm made of black plexiglass) under a low-light setting and allowed to explore for 300 s. The behaviour of each animal was video-recorded and the distance travelled and duration of time spent in the different zones was analysed using Anymaze 5.0. The MWM test was conducted on week 4 (days [22][23][24][25][26][27][28]. Animals (PrL DBS, n = 12; sham, n = 13) received 30 min of electrical stimulation (or sham stimulation) prior to MWM test during 8:00-14:00 h (Fig.…”
Section: Behavioural Protocolsmentioning
confidence: 99%
“…Of particular interest is a single-case report in which electrical stimulation was used to treat a patient with morbid obesity, in which the electrical brain stimulation unexpectedly evoked autobiographical memory episodes in the patient [101]. In animal studies, experimental data showed that memory functions could be enhanced by stimulating the medial prefrontal cortex [102][103][104][105], entorhinal cortex, and perifornical region [106][107][108]. It has also been shown to induce antidepressant-like effects in animal studies [109,110].…”
Section: Alternative Strategies For the Treatment Of Alzheimer's Diseasementioning
confidence: 99%